THE 17TH-18TH CENTURY HANDWRITTEN LEGACY OF THE GREAT SKETE: THE SKETE PATERICON AND SYNODYK - Mykola Kuhutiak (Vasyl Stefanyk Precarpathian National University, 2015)
The paper presents the results of the first extensive national research into the handwritten legacy of the Great Skete (Maniava Skete); it deals with historical and archeological aspects of Патерик Скитський (the Skete Patericon) and Синодик (the Synodyk, or memorial book); the latter manuscript was discovered by the author of this paper in the Romanian Academy Library. The Skete Patericon comprises 'Житіє Іова' ('The Life of Job'), 'Завіт Духовний' ('Spiritual Testament') and 'Регула' ('Regula').  The paper highlights a unique role of the Skete in the life of the Orthodox Church, in the religious life of the 17th-18th century Ukraine, in reviving and preserving national spiritual traditions.